Menuju Pembangunan Partisipatif (bagaimana Mendayagunakan Kebudayaan Lokal) - Irwan Abdullah (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1997)
Grassroot people are development actors who determine course of development so that it will bring about a more valuable change. That is the basic argument as why people autonomy and participation are the keywords for the development achievement. Research and experience showed that development programs and projects failures are usually because lack of people participation. This article is based on the assumption that local culture and local participation should become the guidance for policies and on-going development processes. To improve people participation in development, local culture should be strengthened by : (1) utilizing local social and cultural institutions, (2) ecudating local people, and (3) creating participationâ culture. Development ideas tend to be more implementable if they can be enculturized through traditional institutions such as indigeneous ceremony and religious rituals. People participation can be encouraged through the established institutions so that there is no need to create specific institution to serve government interests. Intensive people education which aimed at renewing people's ideas and knowledge would be more effective to change their apprehension for development. In this important effort , there should also perspective change among bureaucrats. Then, participative culture in all variety should be appreciated and cultivated by giving incentives and rewards for individuals, groups and institutions. As such, development moral should be in accordance with the people moral.